If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -9x = 108 + -44x Solving 13 + -9x = 108 + -44x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '44x' to each side of the equation. 13 + -9x + 44x = 108 + -44x + 44x Combine like terms: -9x + 44x = 35x 13 + 35x = 108 + -44x + 44x Combine like terms: -44x + 44x = 0 13 + 35x = 108 + 0 13 + 35x = 108 Add '-13' to each side of the equation. 13 + -13 + 35x = 108 + -13 Combine like terms: 13 + -13 = 0 0 + 35x = 108 + -13 35x = 108 + -13 Combine like terms: 108 + -13 = 95 35x = 95 Divide each side by '35'. x = 2.714285714 Simplifying x = 2.714285714
| x+4(16)=16 | | -26.34+42.18=x | | 4xX=6 | | 45=9*1 | | 5+2y-2=9y+12-6y | | 17x+8+9x-9=2x+23 | | 3x+1/3-13/2=1-x/4 | | 2(x-3)=-10 | | -14=8+x | | 2-5(3-y)=2-(4-5y) | | 48=2x-6 | | 1=5p-2-4p | | 4=7x | | 2(6-8x)=4(2x-3) | | -11x+22=45 | | r+0.27=-0.59 | | 6(-x-2)=48 | | r+0.27=-0.25 | | -7x+6=48 | | 2(x+1)=3(x+7)-12 | | 2x/3=6-x/4 | | 25x^2-129=0 | | 3(2+x)=2(2+x) | | x^3+10x^2+13x+24=0 | | 2(x+1)=3(x+7) | | x-2(6)=2 | | 3s^2=2s^2+1 | | 5x+4=-x-20 | | -10x-4x+13x=0-7 | | 5x-7(x-4)=51 | | 14x=(5x+14) | | y=xk |